PRAGMATIC SIGNS OF ORNITHONYMS IN PROVERBS IN UZBEK AND ENGLISH LANGUAGES - Nargiza Maxmudova (Galaxy International Interdisciplinary Research Journal, 2022)
The article describes the ornithonyms in the example, parables and phraseological units and the specifics of the meaning in Uzbek